Is a Bond Rating Downgrade Bad News, Good News, or No News for Stockholders? - GOH, Choo Yong, Jeremy (Institutional Knowledge at Singapore Management University, 1993)
We examine the reaction of common stock returns to bond rating changes. While recent studies find a significant negative stock response to downgrades, we argue that this reaction should not be expected for all downgrades because: (1) some rating changes are anticipated by market participants and (2) downgrades because of an anticipated move to transfer wealth from bondholders to stockholders should be good news for stockholders. We find that downgrades associated with deteriorating financial prospects convey new negative information to the capital market, but that downgrades due to changes in firms' leverage do not.